Effect of Ni content over Ni-Mg-Al hydrotalcite structure - Ravi Shanker Ahuja Ravi; Annabathini Geetha Bhavani; Tanveer Ahmad Wani Tanveer; Tara Prasad (Zaštita Materijala)
Hydrotalcite powder materials have well demanded applications in various fields. The Ni-Mg-Al hydrotalcite materials are prepared through co-precipitation method by varying the Ni amounts. The Ni ratios of 0.1, 0.2, 0.3 and 0.4 results the materials of Ni0.1Mg0.60Al0.34, Ni0.2Mg0.60Al0.34, Ni0.3Mg0.40Al0.34, Ni0.4Mg0.30Al0.34 are obtained at pH of 9.3.  The calcined hydrotalcite materials are analysed through BET, XRD and SEM. The observations are well in correlation between the materials. Increase in Ni amount of 0.2 leads the optimum level of loading in hydrotalcite structure which may lead the inter-layer platelets spacing and reduces the surface area.